Examining teacher-made English test in a language school - Taufiq Effendi; Ilza Mayuni (Mitra Palupi, 2022)
Background: Multiple-choice, teacher-made English tests have constantly been popular due to their immediate alignment to classroom instructions. However, ample studies have indicated the need for continuous evaluation of their quality to allow evidence-based feedbacks for sustained betterment of assessment practices. Purpose: This study sought to examine the quality of a multiple-choice, teacher-made English formative informal assessment for four classes of high school students of an English course in Madura, Indonesia.Design and methods: Data were collected from the test results of eighty students and put in an excel document. The data were then analysed with a computer application called Conquest to analyse the responses of each of the students on every item of the test. Based on this item response analysis, it turned out that the test could have achieved a higher credibility if necessary, moderations had been taken. Results: The findings recommend that schools as well as teacher institutions need to provide necessary trainings to ensure in-service teachers and pre-service teachers possess adequate test development and test analysis expertise for continuous improvement of the learning, teaching and assessment practices.